Partisipasi Stakeholders Dalam Capaian Program Desa Mandiri Pangan di Desa Wukirharjo Kecamatan Prambanan Kabupaten Sleman - Krisnadi, Agus; Budiati, Lilin (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
Program Desa Mandiri Pangan –Demapan (Food Self-Sufficient Village program) is one the government’s initiatives aimed to build self sufficiency of food in a region. However, the importance of participation in development processes in the villages has not been fully understood and carried out by the stakeholders, be it the government, the private sector, the NGOs or the community. This program has been carried out in Sleman Regency since 2009 comprising four stages, whereas year 2012 is planned as the self-sufficiency year. The study examines several variables including (1) level of participation, (2) methods/techniques of participation, (3) intensity of participation and (4) barriers/constraints of participation. Analysis showed that the key stakeholders in the implementation of the program included (1) Tim Pangan Desa (Village Food Team), Lembaga Keuangan Desa (Village Finance Institution), Kelompok Afinitas (Affinity Group), Pengurus Lumbung Pangan (Food Stock Committee) and the private sector. However, the role of the private sector is considered to be lacking. Low level of participation from the village administration is found to have reduced the level of trust, resulting in poor communication. Musyawarah (discussions), dialogues and negotiations should be carried out by the village administration to improve communication among stakeholders to ensure the replicability of the program in the surrounding villages and areas sustainably.